2017
DOI: 10.1155/2017/1360565
|View full text |Cite
|
Sign up to set email alerts
|

Rat Liver Enzyme Release Depends on Blood Flow‐Bearing Physical Forces Acting in Endothelium Glycocalyx rather than on Liver Damage

Abstract: We have found selective elevation of serum enzyme activities in rats subjected to partial hepatectomy (PH), apparently controlled by hemodynamic flow-bearing physical forces. Here, we assess the involvement of stretch-sensitive calcium channels and calcium mobilization in isolated livers, after chemical modifications of the endothelial glycocalyx and changing perfusion directionality. Inhibiting in vivo protein synthesis, we found that liver enzyme release is influenced by de novo synthesis of endothelial glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Mechanoreceptors transform this mechanical signal into a biological one [ 46 , 47 ]. Intracellular pathways activated by shear stress include stimulation of transmembrane proteins, activation of ion channels, intracellular calcium mobilization, Notch1 signaling, activation of the transcription factor KLF2, expression of vascular cell adhesion molecule 1 (VCAM-1) and CD44, as well as c-fos, c-myc and c-jun [ 26 , 48 , 49 , 50 , 51 ]. These molecular responses are crucial to ‘prime’ the hepatocytes for liver regeneration [ 5 ].…”
Section: Lsec During Regeneration After Partial Hepatectomymentioning
confidence: 99%
“…Mechanoreceptors transform this mechanical signal into a biological one [ 46 , 47 ]. Intracellular pathways activated by shear stress include stimulation of transmembrane proteins, activation of ion channels, intracellular calcium mobilization, Notch1 signaling, activation of the transcription factor KLF2, expression of vascular cell adhesion molecule 1 (VCAM-1) and CD44, as well as c-fos, c-myc and c-jun [ 26 , 48 , 49 , 50 , 51 ]. These molecular responses are crucial to ‘prime’ the hepatocytes for liver regeneration [ 5 ].…”
Section: Lsec During Regeneration After Partial Hepatectomymentioning
confidence: 99%
“…Once the need for oxygen delivery to the liver was overcome, perfusion flow was maintained at 0.9 mL min − 1 g − 1 liver weight (6 mL min − 1 ), which is within the range that ensures normal portal pressure and perfusion flow in the isolated rat liver [30], and is close to physiological portal blood flow in the rat (1.25 mL min − 1 g − 1 liver weight) [31]. These conditions preserve the sinusoidal endothelium from shear stress [32], which can trigger the release of hepatic enzymes [33]. The bile duct was not cannulated, as recommended, to avoid accidental cholestasis and its unpredictable influence on the kinetics of hepatic BR uptake [34].…”
Section: Isolated Perfused Rat Livermentioning
confidence: 74%
“…The tests were performed as described in detail [22]. Liver perfusion effluent was assayed for a marker of membrane lipid oxidation (malondialdehyde), which was undetectable in contrast to oxygenated liver perfusion [33]. There was no apparent membrane permeabilization (ATP release) or cytolysis (LDH release) (Suppl.…”
Section: Viability Tests On Isolated Perfused Rat Livermentioning
confidence: 99%
“…Studies have shown that elevated activities of these cytosolic enzymes indicate hepatocyte or other cell type damage [15]. However, the ALT is more specific to liver and better use in the diagnosis of liver injury particularly in dogs and cats [16].…”
Section: Discussionmentioning
confidence: 99%